Strain energy calculations of hexagonal boron nanotubes: An ab-initio approach - Jain, S.K.; Srivastava, P. (Condensed Matter Physics, 2013)
An ab initio calculations have been carried out for examining the curvature effect of small diameter hexagonal boron nanotubes. The considered conformations of boron nanotubes are namely armchair (3,3), zigzag (5,0) and chiral (4,2), and consist of 12, 20, and 56 atoms, respectively. The strain energy is evaluated in order to examine the curvature effect. It is found that the strain energy of hexagonal BNT strongly depends upon the radius, whereas the strain energy of triangular BNTs depends on both radius and chirality.